Peningkatan Pengetahuan tentang Latihan Relaksasi Autogenik untuk Menurunan Nyeri pada Pasien Post Operasi Apendiktomi - Romauli E.G. Siallagan; Khairunnisa Batubara (Lembaga Pengembangan Kinerja Dosen, 2025)
Appendicitis ranks highest among emergency cases in the abdomen if not treated immediately will cause severe infection until the intestinal lumen can rupture. Pain will appear as a nursing problem for patients who have undergone appendectomy surgery because it is an act of removing the infected appendix through surgery. Pain can be minimized, one of which is with autogenic relaxation training. Activities start from measuring vital signs, pain scale, assessing anxious expressions, then autogenic relaxation training. Education is carried out to assess the knowledge of the community with a history of post-appendectomy surgery about autogenic relaxation and is carried out in collaboration with local village officials. The method used in this activity is counseling about autogenic relaxation training from a team of nursing lecturers and nursing students as many as 36 respondents. The results obtained from respondents before being given education were 36 people who stated that they did not know about autogenic relaxation training and the pain scale felt was above 6 after appendectomy surgery. The output of the PkM that has been implemented is expected to increase knowledge about autogenic relaxation training after autogenic relaxation training is implemented in the community.